Les capacités inférentielles en situation de compréhension de récits : l’importance de s’adapter aux niveaux scolaires considérés - Causse, Lorene; Syssau, Arielle; Blanc, Nathalie (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This study examines the practices of assessment of young children’s inferential abilities during the comprehension of narratives. The objective is to question the presence of developmental differences that are classically reported between different ages assessed using the same story. Rather than only following this same perspective, this study proposes to investigate the relevance of adjusting to the students’ school level to accurately assess their inferential abilities. The inferential abilities of 348 students aged five to eight years old were surveyed, by either using a story that corresponded to their grade level, or using a story from a grade level different from theirs (i.e., higher or lower). The results show that when students at different grade levels are assessed using the same material, they show differences in achievement. However, when students are assessed with a grade-adjusted narrative, no differences are observed between the age groups studied.